Refinements, Generalizations, and Applications of Jordan's Inequality and Related Problems - Niu Da-Wei (Journal of Inequalities and Applications, 2009)
Abstract This is a survey and expository article. Some new developments on refinements, generalizations, and applications of Jordan's inequality and related problems, including some results about Wilker-Anglesio's inequality, some estimates for three kinds of complete elliptic integrals, and several inequalities for the remainder of power series expansion of the exponential function, are summarized.